The Interaction between Formulaic Language and Linguistic Variability in Authentic Language Use, Exemplified by the Prepositional Multi-Word Ex-pression "unter Geschrei" - Iglesias Iglesias, Nely M. (Revista de Filología Alemana, 2019)
The starting point of this research is the German prepositional multi-word expression (PMWE) unter Geschrei. In analising, one of the main aims is to discover how formulaic language and linguistic variability condition each other when both interact. More precisely, it will be shown which lexical restrictions (constraints) are present in the analysed phraseological unit, especially concerning adjective slots – from a corpus linguistic-perspective. After thorough analyses, the idea is that the more slots vary in authentic language use, the more fixed the syntactic (phraseological) scheme is in the mental lexicon of the speakers of a language community.
Keywords: Prepositional Multi-Word Expressions (PMWE); Formulaic Language; Linguistic Variability; Corpus Linguistics